Kompetensi Motivator dalam Pelaksanaan Pembelajaran Individual System di biMBA AIUEO Jember - Amani Syarifah Aliyah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to describe the competence of motivators in implementing learning Individual System at biMBA AIUEO Jember. A motivator is the term for an educator at biMBA AIUEO Jember. One of the qualifications for a motivator at biMBA AIUEO Jember is a high school/vocational high school education. However, motivators at biMBA AIUEO Jember are capable of implementing learning Individual System according to the guide book Handout. Metode research uses a descriptive qualitative approach with location selection using the technique purposive area. The determination of subjects in this study is informants who are determined using the technique purposive sampling, namely the motivator and the head of the unit as key informants and two parents as supporting informants. Data collection used observation, interviews and documentation. Data analysis was carried out through data collection, data reduction, data presentation and drawing conclusions. Data validity techniques used extended observation, increased persistence and triangulation which included: source triangulation and technical triangulation. The result of the research was four competencies. First, pedagogical competence is reflected in the planning, implementation, and assessment of learning that is tailored to the needs of students. Second, personality competence is seen from a calm and wise attitude in handling student dynamics, but there is no communication between the motivator and parents. Third, social competence is seen from the adjustment of learning to the habits and backgrounds of students, although interaction with the head of the unit is still limited and there is no interaction with parents. Fourth, professional competence is seen when the motivator uses the Handout book as a guide for learning implementation and active participation in routine training organized by the biMBA AIUEO center. The conclusion of this research is that two of the four theories explained, there are two competencies that are not fully in accordance with what happened at biMBA AIUEO Jember
Entry oleh Arif 2026 Januari 28
Keywords: Educator Competency; Individual System Learning; Early Chilhood Education